Faktor-faktor yang Berperan terhadap Terjadinya Kecemasan Orang Tua Anak Sekolah Dasar di Desa Maumbi pada Masa Pandemi Covid -19 - Tangkuman, Kristinia M.; Dundu, Anita E.; Kaunang, Theresia M. D. (Universitas Sam Ratulangi, 2021)
Abstract: The 2019 Coronavirus Disease (COVID-19) pandemic has changed the learning pattern to distance learning, which is an online system. Besides their other activities, parents play a more important role in accompaning and guiding their children during online learning than that of the teachers. Therefore, the parents endure uncomfortable feelings such as anxiety due to increased burden. Moreover, there are various factors that can play a role in the occurrence of parental anxiety. During this pandemic, online learning has also penetrated into the countryside. Maumbi village is one of the areas affected by the COVID-19 pandemic. This study was aimed to analyze the factors that contribute to the anxiety of parents of elementary school children at Maumbi village during the COVID-19 pandemic. This was a descriptive and analytical study with a cross sectional design. Data of this study were obtained by using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Samples of this study were 107 parents of elementary school children who met the inclusion and exclusion criteria. The multivariate analysis showed that the factors that contributed to the anxiety level of parents were economic stressors (p=0.021, t count=-2.347, and Î²=-0.224) and occupational stressors (p=0.042, t count=-2.055, and Î²=-0.197). In conclusion, factors contributing to the anxiety of parents of elementary school children at Maumbi village during the COVID-19 pandemic were economic stressors and occupational stressors.Keywords: parentsâ€™ anxiety; level of anxiety; online learning; COVID-19 pandemicÂ Â Abstrak: Pandemi coronavirus disease 2019 (COVID-19) membuat pola pembelajaran berubah menjadi pembelajaran jarak jauh. Disamping kesibukan lainnya, orang tua berperan untuk mendampingi dan membimbing anak ketika berlajar online yang jauh lebih besar daripada guru. Orang tua merasa tidak nyaman seperti kecemasan akibat beban yang bertambah. Berbagai macam faktor dapat berperan terhadap terjadinya kecemasan orang tua anak. Dalam masa pandemi ini untuk pembelajaran daring atau online juga sudah merambah sampai ke pedesaan. Desa Maumbi merupakan salah satu daerah yang tekena dampak pandemi COVID-19. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang berperan terhadap terjadinya kecemasan orang tua anak sekolah dasar di Desa Maumbi pada masa pandemi COVID-19. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Pengumpulan data penelitian diambil dengan kuesioner Hamilton Anxiety Rating Scale (HARS). Sampel penelitian ini ialah 107 orang tua anak sekolah dasar yang memenuhi kriteria inklusi dan eksklusi. Hasil analisis multivariat menunjukkan bahwa faktor-faktor yang berperan terhadap terjadinya tingkat kecemasan orang tua anak SD di Desa Maumbi pada masa pandemi COVID-19 ialah stresor ekonomi (p=0,021, t hitung = -2.347, dan Î²=-0,224) dan stresor pekerjaan (p=0,042, t hitung =-2,055, dan Î²=-0,197). Simpulan penelitian ini ialah faktor-faktor yang berperan terhadap terjadinya kecemasan orang tua anak sekolah dasar di Desa Maumbi pada masa pandemi COVID-19 ialah stresor ekonomi dan stresor pekerjaan.Kata kunci: kecemasan orang tua; tingkat kecemasan; pembelajaran jarak jauh; pandemi COVID-19